2014
DOI: 10.1002/ijc.28693
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analyses of DNA repair pathways, smoking and bladder cancer risk in Los Angeles and Shanghai

Abstract: Tobacco smoking is a bladder cancer risk factor and a source of carcinogens that induce DNA damage to urothelial cells. Using data and samples from 988 cases and 1,004 controls enrolled in the Los Angeles County Bladder Cancer Study and the Shanghai Bladder Cancer Study we investigated associations between bladder cancer risk and 632 tagSNPs that comprehensively capture genetic variation in 28 DNA repair genes from four DNA repair pathways: base excision repai, nucleotide excision repair (NER), non-homologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…The value of FC for improvement of outcome in relation to progression rate and survival remains to be demonstrated. 6.7.5.2. Narrow-band imaging.…”
mentioning
confidence: 98%
“…The value of FC for improvement of outcome in relation to progression rate and survival remains to be demonstrated. 6.7.5.2. Narrow-band imaging.…”
mentioning
confidence: 98%
“…However, a strong association was detected between the Cys326Cys risk genotype and cardiovascular mortality. Although in comparison to studies that have examined the possible association between the OGG1-rs1052133 polymorphism and cancer [18][19][20][21][22][23][24][25][26][27][28][29][30][31] , very few have examined its association with cardiovascular disease [33][34][35]54 , studies in animal models on OGG1 function strongly support this association 32,59,60 . Thus, in a study by Tumurkhuu et al 32 in Ogg1(-/-) mice, the authors observed a more atherogenic profile of the different markers analyzed in comparison with mice with a normal Ogg1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This observation agrees with several functional studies showing that only homozygous carriers of the Cys allele showed a significantly lower DNA repair activity compared to Ser326Ser 16,18 . A potential source of the observed heterogeneity found among studies may be the exposure to different environmental factors [28][29][30][31] (i.e. mainly vegetable intake and other dietary factors).…”
Section: Introductionmentioning
confidence: 99%
“…It has not been measured whether rapid acetylators are more likely to be high intensity/short duration smokers. Moreover, there is heterogeneity in the efficiency of DNA repair pathways between individuals; for example, those who have a slow N-acetyltransferase phenotype have a higher risk of UBC when they smoke (40), and DNA repair processes can also be negatively influenced by longer smoking duration or higher cumulative exposure (in pack-years) (41). This indicates that the DNA adduct pathway of UBC pathogenesis is important in smoking-related UBC.…”
Section: Smoking Behaviour and Molecular Pathways To Bladder Carcinogmentioning
confidence: 99%